An examination of nonverbal behaviours in successful and unsuccessful professional volleyball teams - Durdubas, D.; Martin, L. J.; Koruc, Z. (International Journal of Sport and Exercise Psychology, 2021)
The purpose of this study was to explore the relationship between nonverbal communication and team success in real-time professional volleyball games. The sample included the top four and bottom four teams from the Turkish Men`s Volleyball 1st League from the 2016-2017 season. The development of a coding scheme for nonverbal behaviours (NVBs) was informed by the extant literature and interviews with volleyball experts (n = 5). Video recordings of 24 matches were analysed under three conditions for each team (a win, a loss, and a tie-break game). The findings indicated that successful teams displayed a greater amount of NVBs in total, and used significantly more instructional and supportive NVBs than their less successful counterparts. In addition, successful teams demonstrated more frequent use of instructional NVBs during the games that they won, more supportive behaviours when they lost, and both of these behaviours during tie-break games. Results from the present study highlight the different uses of NVBs between successful and less successful professional volleyball teams, which has both theoretical and practical implications.